CELLULAR PRECIPITATION IN THE Mg- 8 wt.%Al ALLOY - BENSAADA, S.; BENMACHICHE, M.; BOUZIANE, M.T. (Science des matériaux (Laboratoire LARHYSS), 2015)
The reaction of precipitation in alloys of system Mg-Al was the theoretical and experimental investigation object many having contributed to the comprehension of the various mechanisms controlling. The goal of this work is the description, on the one hand mechanisms controlling this reaction and the modifications of the mechanical properties which accompany them at the time of ageing of the alloy Mg-8 mass.% Al with 200°C and on the other hand the effect of the plastic deformation on the kinetics of precipitation. The techniques of analysis used in this respect are: optical microscopy, the diffraction of x-rays and it micro Vickers pyramid hardness. Key words: alloy Mg-Al; precipitation; mechanism; deformation.